PENGARUH PROMOSI JABATAN TERHADAP KINERJA KARYAWAN DIKAJI MENURUT TEORI ALDEFER - Dion Yanuarmawan (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2012)
The main goal of this research is to analyze and explain the effect of job promotion on work motivation, to analyze and explain the job promotion effect on employee performance, to analyze and explain the job promotion effect on employee performance through work motivation, to analyze and explain the influence of motivation to work towards employee performance of PT.BPR Gunung Ringgit Malang.In this research, there are 3 variables: job promotion variable (X), work motivation(Z) and employee performance (Y), which can be classified into two variables, are independent variables and dependent variable. The independent variables consist of the job promotion (X). The dependent variable consists of work motivation (Z) and employee performance (Y). Several data collection methods are used, such as questionnaire, interview and documentation. Data analysis method is Ordinary Least Square (OLS). Supported by SPSS software version 15.0. The respondent is 80 persons. Data analysis results show that the job promotion variable (X) has a positive and significant effect on work motivation (Z). Job promotion variable (X) have an effect on positive and significant impact on employee performance variable (Y). Work motivation variable (Z) has a positive and significant impact on employee performance variable (Y).